Thermally Stimulated Depolarization Currents (TSDC): A sensitive technique for analyzing protein structure. Issue 3 (2010) - Bedotti, R.; Bridelli, M. G.; Capelletti, R.; Polverini, E.
Abstract : The water molecules surrounding proteins as a thin layer and those packaged in pockets and cavities shape and control their structure. Thermally Stimulated Depolarization Currents (TSDC) technique has been applied to investigate the hydration structure of six proteins with different structural motifs: pepsin, β -lactoglobulin, α -chymotrypsin, bovine serum albumin, human serum albumin and myoglobin, at very low hydration level (water vapor activity aw ≈0.80) both in the native state and after treatment in trifluoroethanol/water mixture 80% (v/v). A combined approach based on the use of the TSDC technique, able to distinguish H2 O dipoles belonging to the solvation shell in terms of their order degree and mobility, and of FTIR and CD spectroscopies has allowed us to reexamine the problem of conformational stability of macromolecules as a function of their hydration.